The Post-War Reorganization of the German Banking System - Adler, Hans A. (Quarterly Journal of Economics, 1949)
I. Basic purposes, 322. — II. Attempts at quadripartite agreement, 325. — III. Reorganization in the U. S. Zone, 325. — IV. Reorganization in the French and British Zones, 328. — V. The new Central Bank in the Western Zones, 330. — VI. Reorganization in the Soviet Zone, 333. — VII. The situation in Berlin, 337. — VIII. Conclusion, 339.